WILLINGNESS TO ACCEPT VALUE OF LAND DEVELOPMENT VALUE AS A BASIS FOR CONSERVATION PROGRAM PADDY FIELDS SEKARSULI SUB IN VILLAGE DISTRICT BERBAH SLEMAN - Hamdi Sari Maryoni, Wahyu Hidayati (Jurnal Ilmiah Cano Ekonomos, 2015)
This study discusses the conversion of paddy fields in Sleman are constantly increasing overtime. Sleman District Government to establish areas of productive agricultural centers to maintainthe ability to produce food, especially rice. The subjects were farmers who have land in the village ofas many as 35 people Sekarsuli obtained using snowball sampling. Paddy land conservation programwill be sustained when the value of the program is received and in accordance with the expectationsof landowners. One model is the determination of the value of conservation programs is the value ofland development rights. Value of land development rights is the difference between the expectedvalue of the optimal land to the value of land. Estimates of the value of further land developmentrights offered to landowners if they agreed that if the value was used as the basis of determining thevalue of land conservation programs. Conclusion: (1) based on the estimates obtained by the averagevalue of land amounting to 55 percent of the estimated value of the optimal land. The amount ofexcess is an average of 45 percent, hereinafter referred to as the value of land development rights(Value Development Right). (2) Respondents who agreed with conservation programs by 24respondents, while the other does not agree as much as 11 respondents. The land area and distancelands to public facilities be an influential factor on the landowner's decision to accept or reject theprograms offered.